The practice of building condition assessment in public sector facility management - Syamilah Yacob,; Azlan Shah Ali,; Cheong, Peng Au-Yong (Penerbit Universiti Kebangsaan Malaysia, 2018)
The Total Asset Management Manual (TAMM) is introduced and implemented by Government of Malaysia to manage the government assets. The implementation of public sector facility and asset management is crucial and important to ensure the government building well managed and can serve the purpose for which it is constructed. Therefore, it is important to the professionals involved in managing the asset or facility to know and competent in the related field especially building condition assessment (BCA). The Standard guideline for BCA for Existing Building (JKR 21602-0004-13) is developed as a part of support document for TAMM. The purpose of this research is to conduct a review of the BCA practice in government buildings. The aim is to improve the government service delivery toward effective decision making for building maintenance. The research methods consisted of literature review and a quantitative approach to gather the observational data through inspection of three (3) Malaysia public office buildings. Inspections were performed by 42 building inspectors and the findings were analyzed by using Building Condition Assessment Rating System (BCARS). The total number of 1,745 defects have been identified with two (2) buildings at a good condition with a rating B at score 8.45 and 8.18 and one (1) building with C score 13.38 at fair condition. The results are then used to determine the need and remedial action to assess and maintain the desired level of service to improve the building facilities condition.